Pengembangan Usaha Melalui Blue Ocean Strategy (Bos) Di Home Industry Liya - Agantha, Mukhlis Yagi, Dr. Suranto, MM (2016)
This research was conducted at the company as one of the manufacturers LIYA suttlecock in Solo area. Producing suttlecock with quill LIYA main ingredient is labor-intensive industries are still using manpower or manually in the running production process. The Business Model Canvas meupakan mendiskriptifkan tool for companies with a complete and understand the workings of LIYA. BMC will show the real conditions that occur in business processes LIYA with simple and able to understand and easy to prepare the strategy developed in the business. In this method the business process is divided into nine blocks that will explain the existing business processes: customer segment, value propotitions, channels, customer relationships, revenue streams, key resources, key activities, key partnership cost structure. Results from the descriptive LIYA didapatka through discussions and interviews will be optimized with Blue Ocean Strategy method approach to the development of strategies for the company. Blue ocean strategy itself is a strategy to create new market space for LIYA that are not in the business market hard, tight and crowded by competition. LIYA will be able to create value innovation with the implementation of Blue Ocean Strategy, with a canvas-making strategies and frameworks eliminate-reduce-add-create. Pendiaknosa strategy canvas as the real conditions in the market for the products LIYA. By creating a new movement will create marketing strategies that do LIYA more ahead of other companies. Promotion, to gor gor, and making the web will be a distinguishing attribute capable of carrying LIYA the blue ocean. The existence of a new strategy for the company will be able to increase competitiveness in existing markets and further establish the new market.